Microstructure and Thermal Conductivity of Sintered Reaction-Bonded Silicon Nitride: The Particle Size Effects of MgO Additive - Shin-Il Go; Yinsheng Li; Jae-Woong Ko; Ha-Neul Kim; Se-Hun Kwon; Hai-Doo Kim; Young-Jo Park (Advances in Materials Science and Engineering)
The particle size effect of MgO as a sintering additive on the thermal conductivity of sintered reaction-bonded silicon nitride (SRBSN) was investigated. It was revealed that the size of MgO is critical for thermal conductivity with regard to the microstructural evolution process. That is, the abnormal grain growth promoted by an inhomogeneous liquid-phase distribution led to higher thermal conductivity when coarser MgO was added, whereas a relatively homogeneous liquid-phase distribution induced moderate grain growth and lower thermal conductivity when finer MgO was added.